A Review on the Electrochemical Behavior of Titanium Improved by Nanotubular Oxide Obtained via Anodization for Biomaterial Applications - Al-Swayih , A. A. (Progress in Chemical Science Research Vol. 6, 2023)
Titanium oxide nanotubes are gaining popularity in a variety of applications, including solar energy, sensors, catalysts, and biomaterials. We review the electrochemical behaviour of titanium oxide nanotubes prepared by anodization in simulated body fluids in this chapter. TiO2 nanotube electrochemical behaviour is determined by its morphology and surface properties. These surface characteristics of titanium oxide nanotubes generated by anodization depend heavily on two elements: the anodization process parameters and the electrolyte conditions used. To optimise titanium oxide nanotube with required qualities for particular application, these factors must be properly chosen.